The High Toll of Traffic Injuries : Unacceptable and Preventable - World Bank (World Bank, Washington, DC, 2018)
An estimated 1.25 million people are killed on the world’s roads every year, and between 20 and 50 million people are seriously injured. Every traffic crash is an individual loss. When death or serious injury results, this loss is compounded by the harm to people, households, and social networks. But what is the impact of road traffic injuries (RTIs) on the economic well-being of countries, particularly in low- and middle-income countries (LMICs) that are already struggling to address the needs of large populations in poverty? By estimating the macroeconomic and welfare effects of road traffic injuries, the report tries both to deepen the analysis and to address the needs of two important groups of government stakeholders. Officials responsible for national infrastructure are interested in evaluating road safety interventions as economic investments. For these stakeholders, a key question is the relationship between the reduction of road injuries and national income growth as measured by GDP metrics. Public health officials, meanwhile, are focused on promoting health, preventing road traffic injuries and deaths, as well as on reducing their health and social burden. These two analytical perspectives illuminate and complement each other, although they each apply a different methodology for the measurement of economic impact. The present report thus attempts to address these specific aspects of economic impact, while providing a comprehensive overview of the challenge in estimating the social impact of RTIs.